A comparative study on psychological distress and associated factors among mothers of severely acute malnourished children belonging to urban and rural area of Central India - Yadav, Shobhana; Shukla, Yogesh (Asian Journal of Medical Sciences, 2022)
Background: Psychological distress commonly presents as comorbidities but is often unrecognized in clinical practice or undertreated as comorbidities in mothers of severe malnourished children. There is wide difference in psychological distress and associated factors among rural and urban area. Aims and Objectives: The objective of study was to compare the psychological distress and associated factors among the mothers of severely acute malnourished children belonging to urban or rural areas. Materials and Methods: This cross-sectional study was conducted on total 450 mothers of severely acute malnourished children admitted in nutritional rehabilitation centers (NRCs) of the central India from April 2019 to July 2020 using General Health Questionnaire. Results: Out of total 450 mothers, 94.7% (426) of mothers shown normal psychological state whereas 24 (5.3%) mothers shown probable case of psychological distress. Among the study participants, mean age of the mothers was found 23.54 years (SD 2.43). Majority of mother 311 (69.1%) belongs to rural area followed by 139 (30.9%) from urban area. Majority of the mothers 231 (51.3%) were from Scheduled Tribe caste followed by 123 (27.3%) other Backward Class caste. Majority of the mothers 404 (89.8%) were unemployed in our study. Conclusions: In the rural locality caste of the mother, primary caretaker of the child and money spent at health facility were the significant risk factors for the psychological distress among the rural mothers while in urban locality, wages loss during stay period at NRC and comorbidity present in the child were the significant risk factors for the psychological distress.